“Political engineering”: Continuity and novelty in political theory - Asfar, Muhammad; Affandi, Mochamad Arif; Asfar, Ais Shafiyah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
This article discusses the development of the study of “political engineering” and the theoretical discourse used to formulate the continuity and novelty of future studies. It begins by identifying previous studies that serve as the theoretical foundation, and a literature review method is employed to identify the similarities and differences among existing studies, which are then used to formulate new conceptions. The findings indicate that the perspective of “political engineering” has a strong basis and foundation to be developed as a major field of study in Political Science. This is not only due to the variety and development of studies in recent decades, but also because the needs for political science to transform into applicable, practical knowledge capable of addressing contemporary challenges are increasingly urgent. The conception of “new political engineering” focuses on behavior engineering, using psychological mechanisms referred to as hope and fear, directly targeting actors (with or through institutions) and no longer making political institutions the main object of study. Instead, it extends to campaign messages, marketing management, system functions, political institutions, policy products, and policymakers to explain and direct voter behavior.